Methylomics analysis identifies a putative STAT3 target, SPG20, as a noninvasive epigenetic biomarker for early detection of gastric cancer. - Kuo-Liang Wei (PLoS ONE, 2019)
Gastric cancer is a leading cause of cancer worldwide. Our previous studies showed that aberrant activation of JAK/STAT3 signaling confer epigenetically silences STAT3 target genes in gastric cancer. To further investigate the clinical significance of this phenomenon, we performed Illumina 850K methylation microarray analysis in AGS gastric cancer cells, and cells depleted of STAT3. Integrative computational analysis identified SPG20 as a putative STAT3 epigenetic target, showing promoter hypomethylation in STAT3-depleted AGS cells. Bisulphite pyrosequencing and qRT-PCR confirmed that SPG20 is epigenetically silenced by promoter hypermethylation in a panel of gastric cancer cell lines including AGS cells, but not in immortalized gastric epithelial GES cells. Expression of SPG20 could be restored by the treatment with a DNMT inhibitor, further suggesting that SPG20 is epigenetically silenced by promoter methylation. Clinically, a progressive increase in SPG20 methylation was observed in tissues samples from gastritis (n = 34), to intestinal metaplasia (IM, n = 33), to gastric cancer (n = 53). Importantly, SPG20 methylation could be detected in cell-free DNA isolated from serum samples of gastritis, IM and gastric cancer patients, having a progressive similar to tissues. Taken together, SPG20, a potential STAT3 target, is frequently methylated in gastric cancer, representing a novel noninvasive biomarker for early detection of this deadly disease.